Amyotrophic lateral sclerosis and retinal changes in optical coherence tomography: A systematic review and meta‐analysis. Issue 9 (22nd August 2022) - Nepal, Gaurav; Kharel, Sanjeev; Coghlan, Megan Ariel; Yadav, Jayant Kumar; Parajuli, Pawan; Pandit, Kamal; Shing, Yow Ka; Ojha, Rajeev
Abstract: Introduction: Increasing evidence suggests Amyotrophic Lateral Sclerosis (ALS) as a widespread pathological process comprising nonmotor features like fatigue, mild sensory symptoms, cognitive decline, and visual impairment. Measurements of retinal nerve fiber layer (RNFL) thickness using Optical Coherence Tomography (OCT) may correlate with the neurodegeneration associated with ALS. In addition to RNFL thickness, other OCT parameters have been explored in the context of diagnosing ALS and predicting disease severity. In this study, we explore the possibility that OCT parameters of patients with ALS may differ significantly from those of healthy controls and thus serve as biomarkers for the disease and its progression. Materials and methods: Between 2010 and 2021, the PubMed and EMBASE databases were examined for English language literature. ALS severity was assessed using the revised ALS functional rating scale (ALSFRS‐R). The pooled mean differences in RNFL thickness between ALS patients and controls were calculated using the Standard Mean Difference (Hedges's g ) with a 95% confidence interval (CI) in STATA software version 16. Results: Eleven studies were reviewed for data collection. RNFL thickness was not statistically significantly different between ALS patients ( n = 412) and controls ( n = 376) (Hedges's g = –0.22; 95% CI: –0.51 to 0.07, I 2 = 73.04%, p = .14). However, the thickness of inner nuclear layer was significantly different between ALS patients and controls (Hedges's g = –0.38; 95% CI: –0.61 to 0.14, I 2 = 14.85%, p = .00). Conclusion: Our meta‐analysis found that RNFL thickness as a whole or by individual quadrants was not significantly different between ALS patients and controls while the inner nuclear layer (INL) was substantially thinner.